Halal Logistic in Indonesian Culinary MSMEs: An Intersection Between Operational Performance and Sharia Law - Fauzan, Tribowo Rachmat; Sudrajat, Ajeung Syilva Syara Noor Silmi (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
Halal logistics plays an important role in ensuring compliance with sharia law in Indonesia's culinary Micro, Small, and Medium Enterprises (MSMEs). Unlike previous research that generally examined halal logistics in large-scale industries, this study specifically focuses on the operational performance of culinary MSMEs, a sector that faces unique challenges in certification, traceability, and risk management. This research uses a quantitative approach to examine the mediating effects of halal certification, supply chain traceability, and halal risk management on operational performance. Data were collected from 292 culinary MSMEs across Indonesia through structured surveys and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The research results show that halal logistics practices significantly mediate the relationship between halal certification and operational performance (β = 0.379; p < 0.001), while supply chain traceability (β = 0.464; p < 0.001) and risk management (β = 0.325; p < 0.001) also have strong positive effects. This research model is able to explain 53.4% of the variation in operational performance (R² = 0.534), indicating moderate predictive power. These findings confirm the novelty of research in the culinary MSME sector and provide quantitative evidence that halal logistics can improve operational efficiency while maintaining sharia compliance. Practical recommendations are provided for policymakers and business practitioners to develop sustainable halal supply chains, thereby strengthening Indonesia's position in the global halal economy.